Case reportTuberculosis luposa – a case report and literature review - Teresiak, Ewa; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Tuberculosis is still a very common disease and presents a diagnostic and therapeutic problem. The risk of tubercular infection has been estimated to vary from 1 to 2% in developing countries. The most important factors responsible for the increase of incidence of tuberculosis include the presence of pre-existing HIV infection and population migration. The disease usually occurs through haematogenous, lymphatic or contiguous spread. Lupus vulgaris together with scrofuloderma are the most common types of cutaneous tuberculosis. The increased incidence of tuberculosis in developed countries is mostly related to the increase of HIV infections. The diagnosis of lupus vulgaris is usually based on the clinical and histopathological characteristics, often despite the negative results of culture and PCR. The Mantoux test is positive in case of lupus vulgaris and tuberculosis verrucosa. The differential diagnosis includes: sarcoidosis, discoid lupus erythematosus, tertiary syphilis, leprosy, blastomycosis, lupoid leishmaniasis and chronic vegetative pyodermas. Cutaneous infections due to M. tuberculosis and immune reactions to mycobacteria are still common and should always be kept in mind in the differential diagnosis of chronic and resistant inflammatory processes. We present the case of a 68-year old woman with tuberculosis luposa who was diagnosed and treated in the Department of Dermatology of the University of Medical Sciences in Poznań